Midwifery care providers' childbirth and immediate newborn care competencies: A cross-sectional study in Benin, Malawi, Tanzania and Uganda. - Ann-Beth Moller; Joanne Welsh; Christian Agossou; Elizabeth Ayebare; Effie Chipeta; Jean-Paul Dossou; Mechthild M Gross; Gisele Houngbo; Hashim Hounkpatin; Bianca Kandeya; Beatrice Mwilike; Max Petzold; et al. (Public Library of Science (PLoS), 2023)
Evidence-based quality care is essential for reducing sub-Saharan Africa's high burden of maternal and newborn mortality and morbidity. Provision of quality care results from interaction between several components of the health system including competent midwifery care providers and the working environment. We assessed midwifery care providers' ability to provide quality intrapartum and newborn care and selected aspects of the working environment as part of the Action Leveraging Evidence to Reduce perinatal morTality and morbidity (ALERT) project in Benin, Malawi, Tanzania, and Uganda. We used a self-administered questionnaire to assess provider knowledge and their working environment and skills drills simulations to assess skills and behaviours. All midwifery care providers including doctors providing midwifery care in the maternity units were invited to take part in the knowledge assessment and one third of the midwifery care providers who took part in the knowledge assessment were randomly selected and invited to take part in the skills and behaviour simulation assessment. Descriptive statistics of interest were calculated. A total of 302 participants took part in the knowledge assessment and 113 skills drills simulations were conducted. The assessments revealed knowledge gaps in frequency of fetal heart rate monitoring and timing of umbilical cord clamping. Over half of the participants scored poorly on aspects related to routine admission tasks, clinical history-taking and rapid and initial assessment of the newborn, while higher scores were achieved in active management of the third stage of labour. The assessment also identified a lack of involvement of women in clinical decision-making. Inadequate competency level of the midwifery care providers may be due to gaps in pre-service training but possibly related to the structural and operational facility characteristics including continuing professional development. Investment and action on these findings are needed when developing and designing pre-service and in-service training. Trial registration: PACTR202006793783148-June 17th, 2020.